Ecotoxicity studies of two atrazine nanoformulations: From the evaluation of stability in media to the effects on aquatic organisms - Castanha, Rodrigo Fernandes; Pereira, Anderson do Espírito Santo [UNESP]; Villarreal, Gabriela Patricia Unigarro [UNESP]; Vallim, José Henrique; Pertrini, Fernanda Sana [UNESP]; Jonsson, Claudio Martín; Fraceto, Leonardo Fernandes [UNESP]; Castro, Vera Lúcia Scherholz Salgado de (Elsevier, 2023)
In the field of agriculture, nanopesticides have been developed as an alternative to the conventional pesticides, being more efficient for pest control. However, before their widespread application it is essential to evaluate their safe application and no environmental impacts. In this paper, we evaluated the toxicological effects of two kinds of atrazine nanoformulations (ATZ NPs) in different biological models (Raphidocelis subcapitata, Danio rerio, Lemna minor, Artemia salina, Lactuca sativa and Daphnia magna) and compared the results with nanoparticle stability over time and the presence of natural organic matter (NOM). The systems showed different characteristics for Zein (ATZ NPZ) (184 ± 2 nm with a PDI of 0.28 ± 0.04 and zeta potential of (30.4 ± 0.05 mV) and poly(epsilon-caprolactone (ATZ PCL) (192 ± 3 nm, polydispersity (PDI) of 0.28 ± 0.28 and zeta potential of −18.8 ± 1.2 mV) nanoparticles. The results showed that there is a correlation between nanoparticles stability and the presence of NOM in the medium and Environmental Concentrations (EC) values. The stability loss or an increase in nanoparticle size result in low toxicity for R. subcapitata and L. minor. For D. magna and D. rerio, the presence of NOM in the medium reduces the ecotoxic effects for ATZ NPZ nanoparticles, but not for ATZ NPs, showing that the nanoparticles characteristics and their interaction with NOM can modulate toxic effects. Nanoparticle stability throughout the evaluation must be considered and become an integral part of toxicity protocol guidelines for nanopesticides, to ensure test quality and authentic results regarding nanopesticide effects in target and non-target organisms.
Keywords: Agriculture; Aquatic environment; Ecotoxicity; Ecotoxicological assay; Nanoherbicide